Caracterização acústica de grutas turísticas - Casos de estudo em Portugal - António P.O. Carvalho (2015)
Since the Palaeolithic, mankind has been taking advantageof the acoustical characteristics of natural cavesto perform its rituals. Nowadays many of these spaces areused as touristic attractions or even as stage of musicalperformances. This study characterizes three touristiccaves in Portugal where in situ measurements were madeof background noise sound pressure level, RASTI and ReverberationTime. The average RT values were 1.3 to 1.7 sand the RASTI average values revealed good intelligibility(from 0.50 to 0.57). The sound absorption coefficient of thestone that surrounds these caves was also measured in astanding wave apparatus.